H2B monoubiquitylation is a 5′-enriched active transcription mark and correlates with exon–intron structure in human cells - Jung, Inkyung; Kim, Seung-Kyoon; Kim, Mirang; Han, Yong-Mahn; Kim, Yong Sung; Kim, Dongsup; Lee, Daeyoup (Genome Research, 2012)
H2B monoubiquitylation (H2Bub1), which is required for multiple methylations of both H3K4 and H3K79, has been implicated in gene expression in numerous organisms ranging from yeast to human. However, the molecular crosstalk between H2Bub1 and other modifications, especially the methylations of H3K4 and H3K79, remains unclear in vertebrates. To better understand the functional role of H2Bub1, we measured genome-wide histone modification patterns in human cells. Our results suggest that H2Bub1 has dual roles, one that is H3 methylation dependent, and another that is H3 methylation independent. First, H2Bub1 is a 5′-enriched active transcription mark and co-occupies with H3K79 methylations in actively transcribed regions. Second, this study shows for the first time that H2Bub1 plays a histone H3 methylations-independent role in chromatin architecture. Furthermore, the results of this work indicate that H2Bub1 is largely positioned at the exon–intron boundaries of highly expressed exons, and it demonstrates increased occupancy in skipped exons compared with flanking exons in the human and mouse genomes. Our findings collectively suggest that a potentiating mechanism links H2Bub1 to both H3K79 methylations in actively transcribed regions and the exon–intron structure of highly expressed exons via the regulation of nucleosome dynamics during transcription elongation.
10.1101/gr.120634.111